Comparison Between Hypnoanesthesia and Local Anesthesia in Minor Surgery - Amri, Ihyan; Siahaan, Charles; Gunawan, Erik Jaya; Ritunga, Imelda; Tjiptohardjo, Andianto Indrawan (Jurnal Ilmu Kesehatan dan Kesehatan, 2024)
Background: Hypnoanesthesia is a state of anesthesia achieved through hypnosis techniques. Meanwhile, local anesthesia is anesthesia carried out by injecting local anesthetic drugs in or around the surgical site which causes temporary obstruction to the conduction of afferent impulses. Objective: This research was conducted to prove that there is no difference between hypnoanesthesia and local anesthesia in minor surgical procedures, with the indication of pain relief. Methods: The research subjects were patients with benign soft tissue tumors consisting of 40 people who were divided into 2 groups, namely treatment and control. Minor surgical procedures with hypnoanesthesia were performed in the treatment group, while in the control group, minor surgical procedures were performed with local anesthesia using 2% lidocaine. Pain is measured with FPS (Face Pain Scale) and monitored with a vital sign monitor. The intervention process was recorded with camcorder video. Changes in serum levels of excitatory neurotransmitters (Glutamic Acid and Substance P) and inhibitory (Beta Endorphin, Enkephalin, and Serotonin) before and after intervention were analyzed using ELISA (Enzym-Link Immunosorbent Assay) in both groups. Results: In the treatment group, it was discovered that patients did not feel pain after undergoing hypnoanesthesia intervention by providing suggestions for the relief of pain in the area where surgery would be performed. In the control group, patients also did not feel pain after local anesthetic intervention in the area to be operated on. However, the results of research and statistical tests showed that there was no significant difference in changes in Beta Endorphins, Enkephalin, and Serotonin as inhibitory neurotransmitters (p > 0.05) or Glutamic Acid and Substance P as excitatory neurotransmitters (p > 0.05) before and after the intervention in both groups of research subjects. Conclusion: the results of this study show that there is no significant difference between the treatment and control groups, they have equality in the final result, namely the relief of pain.